Gender, structural adjustment and informal economy sector trade in Africa : A case study of women workers in the informal sector of North West Province, South Africa - Phalane, Manthiba Mary (University of Limpopo (Turfloop Campus), 2009)
The thesis, Gender, Structural Adjustment and Informal Economy Sector Trade in Africa: A Case Study of Women Workers in the Informal Sector of North West Province, South Africa, comprises of five chapters{PRIVATE } CHAPTER 1 is mainly introductory and deals specifically with the general orientation of the study as outlined in the background and problem statement. This chapter presents the motivation for the study, main aim and objectives and the significance of the study. It also deals with methodology and attendant problems. The chapter also addresses stages of research such as research design, population and sampling, data collection techniques, data analysis of this study. Finally the limitations of the study are outlined. CHAPTER 2 comprises the literature background for the study. The literature focuses largely on the theoretical orientation of the study and on the position of women in the economy. This chapter is divided into two parts. The first part is more general in the sense that it focuses on theorising gender using the gender approach to make a substantive argument. It also focuses on the different definitions of the informal economy sector and the impact of economic reform measures on women in the informal economy sector. This first part further argues the predominance of women in the informal economy sector. Attention in the literature is also focused on women’s employment opportunities in the informal sector and on the marginalization of women through economic reform measures introduced. Such reform measures have been advanced by government means to improve the economy. The second part attempts to illuminate some characteristics of informal work in South Africa. The unit of analysis here is women and their employment or underemployment in the economy. CHAPTER 3 focuses on the effects of macro-economic reform policies on women in the informal economy sector. This chapter discusses the current neo-liberal economic reforms (i.e. Structural Adjustment Programs (SAPs); Growth Employment and Redistribution-GEAR) that have been imposed by governments all over Africa and beyond in areas such as Latin America and Asia. The chapter also indicates the negative effects of these on the poor (women in particular) and on why economic reforms have hit women hardest in the mainstream economy and in the informal sector. As a concluding argument and points raised, the chapter argues for alternative policy approaches that could be used as references to means of improving the lot of operators in the informal economy sector, especially with regard to women. The point raised in this chapter is that legislation alone does not change attitudes, traditions, trade relations and power relations. Thus, alternatives from a female perspective are outlined here to position the situation of women in terms of accessing resources in terms of the policy climate in South Africa in particular economically. From this perspective one can understand whether or not there is adequate protection and promotion of women’s rights in the economy. CHAPTER 4 consists of the empirical data for the study. The findings of the study from fieldwork on the impact of neo-liberal GEAR on women in the informal economy sector is reported, analyzed and relevant interpretations are made. The findings in this study are presented as raw totals and in percentages, where useful cross-tabulations are carried out to reflect the relevant data, which influenced the findings.Qualitative data analysis method is used to analyse data from in-depth interviews, audio and visual recordings. The data is coded and variables and their relationships are generated using the Statistical Package for Social Sciences (SPSS). Key words and phrases are categorised and underlined for the possibility of salient themes and summaries and possible explanatory statements are made. CHAPTER 5 gives a summary of the findings of the study and the implications thereof. A comparative survey of these findings and those discussed in the literature in chapter 2 is made. Finally, a conclusive statement is made and suggestions and recommendations for improving the informal economy sector as a valuable economic entity for women. The conclusion is that the informal economy sector does help to meet the needs of the general low income population while maintaining women’s economic activities to support their families. Thus, change on the thinking and application of socio- economic policies should start by fully refuting the more male oriented economic ideology premise on which current policy approach is based.
Thesis (Ph.D. (Sociology)) --University of Limpopo, 2009
Keywords: Gender; Structural adjustment; Informal economy sector; Women workers; 305.420968; Women farmers; Women in agriculture; Structural adjustment (Economic policy) -- South Africa